2021
DOI: 10.1007/s10549-021-06326-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and resting-state functional brain networks in breast cancer patients treated with chemotherapy

Abstract: Purpose This longitudinal study aimed to disentangle the impact of chemotherapy on fatigue and hypothetically associated functional brain network alterations. Methods In total, 34 breast cancer patients treated with chemotherapy (BCC +), 32 patients not treated with chemotherapy (BCC −), and 35 non-cancer controls (NC) were included. Fatigue was assessed using the EORTC QLQ-C30 fatigue subscale at two time points: baseline (T1) and six months after complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
2
7
1
Order By: Relevance
“…However, our results contrast with previous studies that showed an association between fatigue and cognitive performance in patients with breast cancer 40,41 . Post hoc analysis of our data indicated that women in the cancer group endorsed significantly more fatigue than men ( F = 34.45, p < 0.001).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results contrast with previous studies that showed an association between fatigue and cognitive performance in patients with breast cancer 40,41 . Post hoc analysis of our data indicated that women in the cancer group endorsed significantly more fatigue than men ( F = 34.45, p < 0.001).…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results contrast with previous studies that showed an association between fatigue and cognitive performance in patients with breast cancer. 40,41 Post hoc analysis of our data indicated that women in the cancer group endorsed significantly more fatigue than men (F = 34.45, p < 0.001). However, given that there was no effect of sex on cognitive performance, the women may have been more resilient than the men with respect to brain health.…”
Section: Discussionmentioning
confidence: 79%
“…According to neuropsychological test, in the NAC group, we found that SAS was significantly reduced at TP1 compared to TP0, which was similar to the results of most previous studies [ 26 28 ]. Breast cancer patients who suffer more negative effects from the disease and treatment in the beginning experience a higher level of anxiety [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…We previously showed that breast cancer survivors have altered brain network connectivity compared to healthy controls and chemotherapy naïve survivors (3)(4)(5)(6)(7)(8)(9). Other groups have subsequently observed similar findings (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 70%